A game theoretic model of green technology rivalry - Bakar, Normizan; Musa, Rusmani; Basri, Bakti Hasan (Universiti Kebangsaan Malaysia, 2013)
The optimal research and development of green technology taxes (subsidies) is analyzed in a three-stage game model of an international Cournot duopoly.The governments simultaneously determine the environmental policies in the first stage.In the second stage, the firms simultaneously determine the green technology levels and set the output in the third stage.One firm exists in a home country and one firm exists in a foreign country that produce homogenous goods and export to the third-market country.By assuming that the green technology involves cost-increasing research and development (R&D), the present study finds that green technology is not overused to minimize the total production costs.